2015
DOI: 10.1590/1983-40632015v4533999
|View full text |Cite
|
Sign up to set email alerts
|

Control of volunteer soybean plants in sunflower crop1

Abstract: Sunflower (Helianthus annuus) sown offseason, after soybean crop (Glycine max), is affected by the competition imposed by volunteer plants. Two experiments were carried out to evaluate the control of volunteer soybean plants in sunflower crops. The sulfentrazone herbicide (75 g ha-1, 100 g ha-1 and 250 g ha-1) causes phytotoxicity to sunflower immediately after application, however, plants recover, with no yield losses. These doses do not cause the total death of volunteer soybean plants, but temporarily paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Saflufenacil phytotoxicity decreased at the other sowing times; however, even at 60 DAA, phytotoxicity close to 40% was observed for the commercial dose, which could lead to yield losses. These results corroborate those of Brighenti (2015), who reported that saflufenacil decreased the plant stand and sunflower yield (kg ha -1 ), with the highest dose also reducing the weight of 1000 achenes. Peanut plants presented a phytotoxicity below 20% only at 60 DAA, with their highest phytotoxicity (40%) observed at 0 DAA ( Figure 2D).…”
Section: Effects Of the Herbicides Saflufenacil And Indaziflam On Agrsupporting
confidence: 91%
“…Saflufenacil phytotoxicity decreased at the other sowing times; however, even at 60 DAA, phytotoxicity close to 40% was observed for the commercial dose, which could lead to yield losses. These results corroborate those of Brighenti (2015), who reported that saflufenacil decreased the plant stand and sunflower yield (kg ha -1 ), with the highest dose also reducing the weight of 1000 achenes. Peanut plants presented a phytotoxicity below 20% only at 60 DAA, with their highest phytotoxicity (40%) observed at 0 DAA ( Figure 2D).…”
Section: Effects Of the Herbicides Saflufenacil And Indaziflam On Agrsupporting
confidence: 91%
“…Soltani et al (2019) reported that halosulfuron applied early POST provided 90% control of GR soybean volunteers in white bean (Phaseolus vulgaris L.) in field studies conducted in Ontario, Canada. Brighenti (2015) reported that volunteer soybean can be a problem weed in sunflower (Helianthus annuus L.) grown in rotation in Brazil, with no selective herbicide available for effective control without sunflower injury.…”
Section: Management Of Herbicide-resistant Soybean Volunteersmentioning
confidence: 99%
“…Other post-emergent herbicides have been reported to be effective in controlling volunteer soybeans such as diquat, paraquat, paraquat + diuron, 2,4-D, atrazine (Dan et al, 2009 andLima et al, 2011 andConcenço, 2014), ametryn and glufosinate-ammonium (Brighenti, 2015). However, for the castor there are studies indicating only viability of 2,4-D associated with glyphosate in the desiccation prior to sowing and paraquat + diquat in a Means followed by the same letter in the column does not differ significantly from each other by Tukey test (p ≤ 0.05).…”
Section: Volunteer Soybean Control With Post-emergence Herbicidesmentioning
confidence: 99%
“…Brighenti (2015) found that Saflufenacil is not effective for the control of volunteer soybean. In this context, limitations may exist in finding herbicides to control dicotyldons, while simultaneously being selective to castor.…”
Section: Introductionmentioning
confidence: 99%